Prevalence and intensify of Toxocara canis eggs in the hair and faecal samples of Dogs in Ilesa and Ibadan,Southwestern.Nigeria - Ayanniyi, Olalekan Opeyemi (zoology,Obafemi Awolowo University, 2023)
xii,75p